Telomeric repeat-containing ribonucleic acid (TERRA) expression in patients with idiopathic pulmonary fibrosis - Manal M. El-Desoky; Asem A. Hewidy; Ahmed M. Fouda; Fatma Azzahraa Hisham (Egyptian Journal of Medical Human Genetics, 2021)
Abstract Background Idiopathic pulmonary fibrosis (IPF) represents a chronic disease with a progressive course. It is characterized by excessive lung scarring that ultimately contributes to irreversible lung function reduction. Interestingly, a type of long non-coding RNA termed as telomeric repeat-containing RNA (TERRA) is linked to fibrosis pathophysiology, including IPF. In this study, the expression profile of TERRA was investigated in IPF patients on radiological diagnosis [unusual interstitial pattern (UIP) in high-resolution computed tomography (HRCT)] to evaluate whether it could be employed as a reliable diagnostic biomarker. Results TERRA expression level was significantly higher in IPF patients over healthy controls. The expression level was significantly inversely correlated with the percentage of forced vital capacity predicted (FVC% predicted). By contrast, it was significantly directly correlated with HRCT reticular extent score. Conclusion TERRA expression is an essential biomarker in peripheral blood of IPF patients, providing a valuable non-invasive tool for IPF diagnosis. Moreover, TERRA expression is strongly correlated with UIP in HRCT reticular extent score.